Isolation and Characterization of Group III Campylobacter jejuni–Specific Bacteriophages From Germany and Their Suitability for Use in Food Production - Steffan, Severin Michael; Shakeri, Golshan; Hammerl, Jens Andre; Kehrenberg, Corinna; Peh, Elisa; Rohde, Manfred; Jackel, Claudia; Plotz, Madeleine; Kittler, Sophie (Frontiers in Microbiology, 2021)
Campylobacter spp. are a major cause of bacterial foodborne diarrhea worldwide. While thermophilic Campylobacter species asymptomatically colonize the intestines of chickens, most human infections in industrial countries have been attributed to consumption of chicken meat or cross-contaminated products. Bacteriophages (phages) are natural predators of bacteria and their use at different stages of the food production chain has been shown to reduce the public health burden of human campylobacteriosis. However, regarding regulatory issues, the use of lytic phages in food is still under discussion and evaluation. This study aims to identify lytic phages suitable for reducing Campylobacter bacteria along the food production chain. Therefore, four of 19 recently recovered phages were further characterized in detail for their lytic efficacy against different Campylobacter field strains and their suitability under food production settings at different temperatures and pH values. Based on the results of this study, the phages vB_CjM-LmqsCP1-4 and vB_CjM-LmqsCP1-5 appear to be promising candidates for the reduction of Campylobacter jejuni in food production settings.